LTE Ağları için Servis Kalitesi Farkında Aşağı Yönlü Çizelgeleme Algoritması: Kenar Kullanıcıları Üzerine İnceleme - Güngör, Vehbi Çağrı; Uyan, Osman Gokhan (Institute of Electrical and Electronics Engineers Inc., 2017)
4G/LTE (Long Term Evolution) is the state of the art wireless mobile broadband technology. It makes use of the OFDM technology to offer high speed and provides the system resources both in time and frequency domain. A scheduling algorithm running on the base station holds the allocation of these resources. In this paper, the performance of existing downlink scheduling algorithms has been investigated in two ways. First, the performance of the algorithms has been investigated in terms of throughput and fairness metrics. Second, a new quality of service-aware (QoS-aware) fairness criterion, which accepts that the system is fair if it can provide the users with the network traffic speeds that they demand, has been proposed and evaluated. In addition, a novel QoS-aware downlink-scheduling algorithm, which increases the QoS-aware fairness and overall throughput of the edge users, has been proposed. © 2017 Elsevier B.V., All rights reserved.
QoS-Aware Downlink Scheduling Algorithm for LTE Networks: A Case Study on Edge Users
Keywords: 4G; Lte; QoS-Aware Fairness; Resource Allocation; Scheduling; Distributed Computer Systems; Mobile Telecommunication Systems; Orthogonal Frequency Division Multiplexing; Quality of Service; Resource Allocation; Scheduling; Signal Processing; Wireless Telecommunication Systems; Fairness Criteria; Mobile Broadband Technology; Network Traffic; Ofdm- Technologies; QoS-Aware; State of The Art; System Resources; Time and Frequency Domains; Scheduling Algorithms